Religiosity, Waqf literacy and income to interest in endowing money: Role of accountability as a moderating variable - Sahrina, Mesi; Hatta, Madani; Simamora, Anna Maria; Puspita, Lisa Martiah Nila (Proceeding International Conference on Accounting and Finance, 2024)
This study examines the effect of religiosity, waqf literacy and income on interest in waqf money and the role of accountability in moderating religiosity, waqf literacy and income on interest in waqf money. This study employed a Structural Equation Modeling (SEM) approach, utilizing a sample of 100 participants from Bengkulu Province. Each regency/city within the province was represented by 10 participants. The findings of this study suggest that religiosity positively influences individuals' interest in waqf money. Additionally, it is observed that waqf literacy also has a positive impact on individuals' interest in waqf money. However, income does not exhibit a positive effect on individuals' interest in waqf money. Furthermore, there has no role of accountability in moderating the relationship between religiosity and interest in waqf money. On the other hand, accountability does play a moderating role in the relationship between waqf literacy and interest in waqf money. Lastly, accountability does not have a moderating role in the relationship between income and interest in waqf money.